2020
DOI: 10.2478/sbe-2020-0052
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Culture and Job Satisfaction Among University Professors in the Selected Central and Eastern European Countries

Abstract: Organizational culture and job satisfaction are the most important factors for any university. Research into how satisfied professors are with university culture is crucial in finding ways to increase job satisfaction in the present as well as the future. The aim of our study is to investigate whether the type of organizational culture has any effect on job satisfaction and whether there are any differences between Serbia, Slovenia, and Bosnia and Herzegovina. The study was conducted on 489 professors at unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…The present study explored the job satisfaction of professors and the factors that influenced their satisfaction, and it revealed that the participants of the current study were moderately satisfied with their job. This finding is supported by personal interviews and corresponds to those of other studies (de Lourdes Machado-Taylor et al, 2016; Du et al, 2010; Nebojša et al, 2020). Furthermore, the current study expands on the literature by providing findings that the overall job satisfaction of professors is determined by the total satisfaction that they derive from their roles in instruction, research, service, and advising.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study explored the job satisfaction of professors and the factors that influenced their satisfaction, and it revealed that the participants of the current study were moderately satisfied with their job. This finding is supported by personal interviews and corresponds to those of other studies (de Lourdes Machado-Taylor et al, 2016; Du et al, 2010; Nebojša et al, 2020). Furthermore, the current study expands on the literature by providing findings that the overall job satisfaction of professors is determined by the total satisfaction that they derive from their roles in instruction, research, service, and advising.…”
Section: Discussionsupporting
confidence: 91%
“…de Lourdes Machado-Taylor et al (2016) found Portuguese academics were satisfied with their academic professions (Mean = 6.30, on a scale 0-10) but not very satisfied in general. Nebojsˇa et al (2020) surveyed 489 professors from universities and colleges in Serbia, Slovenia, and Bosnia and Herzegovina, and they reported that the university professors in these three countries had a moderate level of job satisfaction.…”
Section: Job Satisfaction Of Professorsmentioning
confidence: 99%
“…This is a logical expectation in that a transformational dean/director is likely to create healthy workplace culture for faculty to thrive by displaying and reinforcing normative appropriate conduct including open communication, trust and respect among employees (Bass & Riggio, 2006). A 2020 study by Pavlovic et al helps illustrate this point. They found university academicians/professors in three countries (Serbia, Slovenia and Bosnia and Herzegovina) who perceived their organization to have positive culture were more satisfied.…”
Section: Discussionmentioning
confidence: 94%
“…The model-based kinetic method analyses complex chemical processes with multiple reaction steps ( https://kinetics.netzsch.com/en ). Each reaction step has its kinetic equation and a kinetic triple [ 85 ]. In addition, the model-based approach can display each reactant's reaction rate and concentration for each step [ 86 ].…”
Section: Methodsmentioning
confidence: 99%